The IOE Ratio: Quantifying Organizational Potential in Complex Systems - Barack Ndenga (Publisher, 2025)
The emergence, persistence, and collapse of organization in complex systems remain difficult to quantify using classical thermodynamic variables alone. While entropy production describes irreversibility and dissipation, it does not capture the capacity of a system to sustain structured, stable, and adaptive behavior. In this article, I introduce the IOE ratio (Informed Organizational Efficiency ratio) as a quantitative measure of organizational potential. The IOE ratio expresses the balance between usable information and effective entropy within a system and provides a scalar indicator of whether organization is expected to grow, stabilize, or degrade. I develop the theoretical foundations of the IOE ratio, analyze its properties, and demonstrate its applicability across physical, biological, and computational systems. This work establishes the IOE ratio as a unifying metric for organizational dynamics in complex systems. Keywords Organizational potential; IOE ratio; information and entropy; self-organization; complex systems; non-equilibrium thermodynamics; system stability; emergent structure.
This work introduces the IOE ratio (Informed Organizational Efficiency ratio) as a quantitative framework for assessing organizational potential in complex systems. The IOE ratio captures the balance between usable information and effective entropy, providing a unified indicator of whether organization is expected to grow, stabilize, or degrade. The article develops the theoretical foundations of the IOE ratio, analyzes its properties, and demonstrates its relevance across physical, biological, and computational systems. By offering an operationalperspective on organization, this framework extends entropy-based descriptions and contributes to a more comprehensive theory of self-organization and system stability.